PENERAPAN SANKSI TERHADAP PELAKU TINDAK PIDANA PENCABULAN TERHADAP ANAK YANG DILAKUKAN OLEH PENDIDIK STUDI PUTUSAN NOMOR 113/Pid.Sus/2022/PN Bkt - Niken Angelica Larasati; Sukmareni Sukmareni; Riki Zulfiko (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
Sexual abuse has become a very serious problem not only locally, nationally, but also at the international level. If sexual abuse is a disease of the brain, a sexual problem, it's due to changes in the mechanism in the brain, which generally takes a long time to adapt and recover. This study discusses the application of sanctions against perpetrators of criminal acts of sexual immorality against children committed by educators studying decision number 113/Pid.Sus/2022/Pn Bkt. This research raises two issues, namely what are the legal considerations in making decisions against perpetrators of criminal acts of sexual abuse of children committed by educators? how is the application of sanctions to perpetrators of criminal acts of sexual abuse of children committed by educators studying decision number 113/Pid.Sus/2022/PN Bkt? This study uses a normative juridical method. The data source used is secondary data, namely data obtained through a literature study with primary legal materials, secondary legal materials and tertiary legal materials. Data collection was carried out by (normative juridical) by using library research (library research) which is a data collection tool that is not directed directly to research subjects. The results of the study show that the judge's consideration in giving a decision has been and the application of sanctions against the perpetrators of criminal acts of sexual abuse of children committed by educators on decision number 113/Pid.Sus/2022/PN Bkt is in accordance with applicable regulations, namely Article 183 of the Criminal Procedure Code and Law Number 35 of 2014 regarding Child Protection.